2021
DOI: 10.31616/asj.2020.0074
|View full text |Cite
|
Sign up to set email alerts
|

Neuromonitoring in Cervical Spine Surgery: When Is a Signal Drop Clinically Significant?

Abstract: To identify the clinical significance of different patterns of intraoperative neuromonitoring (IONM) signal alerts. Overview of Literature: IONM is a long-established valuable adjunct to complex spine surgeries. IONM for cervical spine surgery is in the form of somatosensory evoked potential (SSEP) and motor evoked potential (MEP). The efficacy of both modalities (individually or in combination) to detect clinically significant neurological compromise is constantly being debated and requires conclusive suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…A reduction of more than 50% in MEP baseline amplitude elicited by direct cortical stimulation was considered a significant change. Relevant EMG activities reported to the surgeon included spikes, bursts, and trains [2,5,[15][16][17]. Abnormal monitoring results were reported immediately by the electroneurophysiologist to allow the surgeon to suspend the surgery and investigate the cause in real-time.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A reduction of more than 50% in MEP baseline amplitude elicited by direct cortical stimulation was considered a significant change. Relevant EMG activities reported to the surgeon included spikes, bursts, and trains [2,5,[15][16][17]. Abnormal monitoring results were reported immediately by the electroneurophysiologist to allow the surgeon to suspend the surgery and investigate the cause in real-time.…”
Section: Methodsmentioning
confidence: 99%
“…To improve neurologic safety, intraoperative neurophysiological monitoring (IONM) is used to detect and give a chance to reverse the related causes of neurologic complications during spinal surgery [9][10][11][12][13]. Many studies provide alarm criteria of the IONM signal change and confirm its reliability in detecting neurologic complications [14][15][16][17]. However, few of these studies reported a specific surgical procedure related to a significant IONM signal change during surgery.…”
Section: Introductionmentioning
confidence: 99%
“…A retrospective cohort study of 207 patients undergoing cervical spine surgery divided the cases based on their signal changes, with one group experiencing transient changes in SSEP or MEP, another group with sustained changes in either modality, or the last group with sustained changes in both modalities. While fifty-two patients (25%) were initially considered to have experienced signal drops, fifty of these fifty-two cases (96%) were eventually recognized as false positives [8]. This argues for the need to standardize signal loss thresholds representative of true damage.…”
Section: Advantages and Disadvantages Of Neuromonitoring In Spine Sur...mentioning
confidence: 99%
“…Moreover, varying patterns in signal detection for various types of nervous system disturbances have resulted in falsepositive or false-negative results. Several studies have investigated these pitfalls in cervical spine procedures, and current solutions center around the use of multiple modalities to provide as much of a comprehensive picture as possible [8].…”
mentioning
confidence: 99%
“…There has been increasing use of intraoperative neuromonitoring (IONM) for intraoperative evaluation of surgical correction as well as prediction of postoperative neurological changes. [1][2][3][4][5][6][7][8][9][10] One study showed 296% increase in the use of IONM between 2008 (n ¼ 31,762) and 2014 (n ¼ 124,835), along with substantial heterogeneity in clinical application. 11 Multimodality IONM (involving somatosensory evoked potentials [SSEPs], transcranial motor evoked potentials [tcMEPs], and electromyography [EMG]) is now used as a surgical adjuvant to help reduce neurological deficits by detecting neurologic injury while still reversible.…”
Section: Introductionmentioning
confidence: 99%